Analysis of Code Familiarity in Module and Functionality Perspectives - Alves, Francisco Vanderson de Moura; dos Santos Neto, Pedro de Alcântara; Lira, Werney Ayala Luz; Ibiapina, Irvayne Matheus de Sousa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2018)
Maintenance is one of the most important phases in the software life cycle. Usually, during this phase the assignment of tasks to developers is made based on the familiarity degree that they have with the source code related to each task. However, it is not simple nor immediate to infer the relationship between the developers and the source code, especially when it is considered the level of functionality, which may have code archives dispersed in many locations of a project. This work presents an approach to infer the familiarity between developer and source code considering the functionality perspective, a view more appropriate in a real context of software development. The approach was applied during the evaluation of real softwares. Through an analysis of the familiarity between the module and functionality perspectives, it was possible to perceive the gain of information that can be obtained to understand better how it is the familiarity distribution among members of a team.